STUDI KORELATIF: KONTROL DIRI REMAJA DENGAN KECANDUAN MENGGUNAKAN INTERNET - Eka Oktavianto; Endar Timiyatun; Atik Suryati; Atik Badi'ah (Medika Respati : Jurnal Ilmiah Kesehatan, 2021)
Correlative Study: Self-Control of Teenagers with Addictions to Use the InternetBackground : Currently internet users in the world and in Indonesia are increasing. Many teenagers are addicted to using the internet. Self control is thought to influence a person to become addicted or not to use the internet. Objective : to determine the relationship between self-control and the level of internet addiction in adolescents.  Methods : The type of research was descriptive correlative using cross-sectional design. Total sampling technique was used in this study with a total of 88 teenagers in SMK Muhammadiyah 3 Yogyakarta. The instrument used was a questionnaire. Data analysis using the Kendall test.  Results : The majority of respondents had very low self control, as many as 44 respondents (50.0%). The majority of respondents were addicted to using the internet in the high category of 42 respondents (47.7%). Adolescents who have very low self-control will tend to experience addiction to use the internet in the high category of 27 respondents (30.7%). Kendall Tau correlation test results, the results obtained p value = 0.001 (p value <0.05), and the value of r = -435. Conclusion : there is a relationship between self-control and the level of internet addiction in adolescents.